Social Network Analysis in Migration Studies - Gečienė, Ingrida (Sociologija. Mintis ir veiksmas, 2009)
Over the last 20 years, there has been growing interest in social network analysis across a variety of social science disciplines, particularly in sociology, antropology, communication science, health and medicine, managment and political science. The roots of a social network perspective can be found in Simmel and Moreno discovery that the nature of ties themselves rather than the social group per se that lay at the center of many human behaviors. Despite these early insights, social network analysis gain its prominence only with revived interest in social networks as essence of social structure in 1980s (Burt, Bourdieu, Coleman, Putnam, Castells, et al.). This article aims to explore current metodological social network analysis approaches and how they can be succesfully employed in migration studies. It is argued that previuos dominant quantitative social network analysis based on full network and egocentric network analysis nowadays is renewed by social capital theory and social support approach. This new social network perspective allows to investigate how social networks function, how they can be constructed, maintained and reproduced, how are network dynamics across time and space.